1976
DOI: 10.1017/s0003356100031408
|View full text |Cite
|
Sign up to set email alerts
|

Breed differences in body composition of equally mature sheep

Abstract: SUMMARYSheep from the Soay, Finnish Landrace, Southdown and Oxford Down breeds were serially slaughtered at about 40, 50, 60 and 70% of their estimated mature body weight. Breed and sex comparisons were made at these degrees of maturity. Large differences were found in the weight of muscle, fat and bone, total muscle ranging from a mean of 3·3 kg in the Soay to 13·0 kg in the Oxford Down; the corresponding range for dissected fat was 1·2 to 9·2 kg.Most of the breed and sex differences observed at the same degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 5 publications
7
53
1
2
Order By: Relevance
“…no sex interaction with the b coefficient), which is in contrast to other studies who showed rams to have a higher impetus for muscle growth compared to ewes (Fourie et al, 1970;. McClelland et al (1976) showed that at approximately 50 to 60% of maturity ram and female composition was similar which may account for the lack of difference between sexes seen in our analysis. This result was emulated in another analysis (Thompson, Butterfield, & Perry, 1985), although in this case a cross-over effect was seen in…”
Section: Production and Management Effects On Carcass Leancontrasting
confidence: 99%
“…no sex interaction with the b coefficient), which is in contrast to other studies who showed rams to have a higher impetus for muscle growth compared to ewes (Fourie et al, 1970;. McClelland et al (1976) showed that at approximately 50 to 60% of maturity ram and female composition was similar which may account for the lack of difference between sexes seen in our analysis. This result was emulated in another analysis (Thompson, Butterfield, & Perry, 1985), although in this case a cross-over effect was seen in…”
Section: Production and Management Effects On Carcass Leancontrasting
confidence: 99%
“…Cunha et al (2000) também não encontraram diferenças significativas entre cabritos Saanen e mestiços Boer x Saanen para peso ao abate, rendimento de carcaça quente e rendimento comercial, tendo em vista o tamanho e o peso adulto à maturidade de animais da raça Saanen. Segundo McClelland et al (1976), grande parte das diferenças na composição corporal entre grupos raciais ao mesmo peso simplesmente reflete diferenças de maturidade relativa entre raças, justificando os resultados obtidos, uma vez que as raças Moxotó e Canindé, segundo a Associação Brasileira dos Criadores de Caprinos (ABCC, 2000), apresentam tamanho e peso semelhantes à maturidade.…”
Section: Resultsunclassified
“…III), suggesting that the former were less mature [13,27]. However, the results obtained for carcass total separable fat (SF) do not support this conclusion.…”
Section: Breed Effectmentioning
confidence: 91%